Outbreak of Vancomycin-Resistant Enterococcus in a NICU: Insights into Molecular Detection and Infection Control - Francesco Peracchi; Giovanna Travi; Alice Proto; Elena Nicolini; Andrea Busni; Luca Mezzadri; Livia Tartaglione; Alessandra Bielli; Elisa Matarazzo; Giorgia Casalicchio; Cecilia Del Curto; Roberto Rossotti; et al. (Microorganisms)
Vancomycin-resistant enterococci (VRE) are a major cause of healthcare-associated infections (HAIs). However, the clinical significance of VRE colonization and the subsequent risk of VRE infection in hospitalized patients are not fully established. Prolonged hospital stays have been observed in neonates colonized by VRE. The mortality rate in pediatric patients with VRE infections ranges from 0% to 42% in both endemic and outbreak settings, often occurring in VRE-colonized neonates. Host and bacterial factors associated with a worse outcome are not fully understood yet. We describe an outbreak of VRE colonization in 21 newborns admitted to our neonatal intensive care unit in January 2024. Microbiological analyses on rectal swabs were performed using molecular testing and culture. Results: In January, VRE was first detected in the urine culture of a 3-week-old patient, followed by a subsequent positive rectal swab result. In accordance with our infection control policy, all the NICU patients were tested, leading to the identification of another 12 colonized patients. The implementation of molecular testing led to rapid VRE identification and the subsequent isolation of colonized neonates, which promptly contained the outbreak. The median time from NICU admission to colonization was 34 (6–37) days. Only one patient developed a CVC-related bloodstream infection, which was successfully treated with linezolid and CVC removal. No VRE-related deaths occurred, even among three patients who underwent abdominal surgery (one gastroschisis, one incarcerated abdominal hernia, and one umbilical hernia) and one patient with necrotizing enterocolitis. Our data show a low infection rate (4%) among VRE-colonized patients (4%) during a NICU outbreak. The rapid identification of multidrug-resistant genes by molecular testing may be implemented in specific settings to enable timely patient identification, adopt infection control measures, and administer appropriate antimicrobial therapy.